Using Reflective Journals to Characterize Pre-Service Teacher Professional Noticing Skills. Issue 4 (2nd October 2021) - van den Kieboom, Leigh A.
Abstract: This study examined professional teacher noticing in the context of written responses 12 pre-service teachers (PSTs) provided in a reflective journal after posing addition and subtraction problems for students in an after-school tutoring program. Professional teacher noticing skills, attending, interpreting, and deciding, were situated within the well-defined mathematics content and associated trajectory of student strategies for the meaning of addition and subtraction. A three-point rubric was designed and utilized to analyze PST attending, interpreting, and deciding responses. Results characterize what PSTs "could do" relative to each skill as well as development of noticing skills over time. Results also highlight how PSTs included a rationale and next steps in deciding responses that related to supporting student understanding of the meaning of addition and subtraction, providing additional practice, and teaching solution strategies. Implications for teacher education are discussed.